Landscape – A Representation of The Spiritual World - Karimboyeva Charos (International Journal Of Literature And Languages, 2026)
The role of psychological and spiritual imagery in poetry is very large. The concept of psychological and spiritual imagery includes the art of depicting the spiritual world, inner world, dreams and thoughts, lyrical experiences, moods and aspirations of a lyrical hero on the basis of high artistry. This article analyzes the combination of psychological and spiritual imagery with landscape imagery in the poetry of Bakhtiyor Genjamurod through his poems on the theme of the Motherland.